2023
DOI: 10.3390/ijerph20031909
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of Parents of Children with Cerebral Palsy Towards COVID-19 Vaccination

Abstract: Children with cerebral palsy (CP) are at a greater risk of respiratory complications from coronavirus disease 2019 (COVID-19). Therefore, this study aimed to assess parental COVID-19 vaccine hesitancy (VH) among parents of CP children in Egypt, using the Arabic version of the Parental Attitude about Childhood Vaccination (PACV) questionnaire. This cross-sectional survey study was conducted at the outpatient clinics of two hospitals in Cairo, Egypt. Parents of children with CP were recruited using a simple rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 51 publications
1
10
0
1
Order By: Relevance
“…The survey revealed that parents with a lower COVID-19 vaccine-related safety concerns had 37% lower odds of being high-hesitant than those with higher concern and those who delayed at least one shot of a recommended vaccine for their child were 2.33 times more likely to be high-hesitant. This finding is consistent with those observed in previously conducted surveys ( 49 , 51 ). Moreover, delayed of at least one shot of a recommended vaccine for their child underlined the need of targeted activities through a better parent-physician communication that may be crucial toward enhancing vaccination coverage.…”
Section: Discussionsupporting
confidence: 94%
“…The survey revealed that parents with a lower COVID-19 vaccine-related safety concerns had 37% lower odds of being high-hesitant than those with higher concern and those who delayed at least one shot of a recommended vaccine for their child were 2.33 times more likely to be high-hesitant. This finding is consistent with those observed in previously conducted surveys ( 49 , 51 ). Moreover, delayed of at least one shot of a recommended vaccine for their child underlined the need of targeted activities through a better parent-physician communication that may be crucial toward enhancing vaccination coverage.…”
Section: Discussionsupporting
confidence: 94%
“…Due to declining vaccination rates and the rise of anti-vaccination campaigns, the world is currently dealing with a number of outbreaks of infectious diseases that represent a threat to children's health and can be prevented by vaccination (7). The anti-vaccine attitude has been extended to lowand middle-income countries (LMICs) of the EMR, specially against coronavirus disease 2019 (COVID-19) among adults (8)(9)(10), and parents (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…In the EMR, parental VH toward routine immunization and COVID-19 has been investigated, but limited studies specifically addressed the influenza VH (12,(16)(17)(18). In the United Arabs of Emirates (UAE), only 12% of the caregivers were hesitant to give their children routine vaccines (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported high rates of vaccine hesitancy and rejection in the region either towards the primary series of vaccination [ 31 34 ] or the booster dose [ 35 , 36 ]. This negative attitude towards COVID-19 vaccination has also affected parents’ willing to vaccinate both healthy and diseased children against COVID-19 [ 37 , 38 ]. The negative attitude towards COVID-19 vaccination may be due to different reasons such as lack of trust in safety, effectiveness, and efficacy of the vaccine or mistrust in health care system itself [ 39 ].…”
Section: Discussionmentioning
confidence: 99%